Comparison of different methods of constructing housing start index in the Philippines - Hebron, Felicidad D. (University of the Philippines, 2009)
Abstract (The possibility of constructing housing index using three different methods or approaches with a fixed base year is explored in this study. Housing start is the start of construction when excavation begins for the footings or foundation of a building. It is considered as the leading indicator of economic activities. In the Philippines, researchers and planners uses data on building permits to monitor construction sites where economic activities are expected to follow. Suppliers of construction materials such as cement, lumber, steel and the like rely on these data for future investment. Other business like banks and food chains also use these data as proximate indicators of supply and demand for investment. Evaluation of the three different methods of index construction is conducted through the fitting of a mixed model, to account the empirical relations between the index and other economic indicators they usually lead. There is a strong space-time association between the index and other indicators, confirming the relationship between the economic boom and housing start index. There is evidence that the index is capable of leading some key economic indicators).